Equal access to care and nurse navigation leads to equitable outcomes for minorities with aggressive large B‐cell lymphoma. Issue 21 (21st July 2021) - Hu, Bei; Boselli, Danielle; Pye, Lisa M.; Chen, Tommy; Bose, Rupali; Symanowski, James T.; Blackley, Kris; Moyo, Tamara K.; Jacobs, Ryan; Park, Steven I.; Soni, Amy; Avalos, Belinda R.; et al.
Abstract : Background: Aggressive large B‐cell lymphomas (LBCLs) are curable, but previous studies have shown inferior outcomes in minorities. Nurse navigation programs can improve patient outcomes by providing patient support. This study presents the outcomes of White and minority patients with aggressive LBCL at an institution with an active nurse navigation program. Methods: The authors prospectively collected baseline characteristics, treatment regimens, and outcome data for patients with aggressive LBCL. Navigation encounters were characterized as low or high intensity. Overall survival (OS) and progression‐free survival (PFS) were calculated with Kaplan‐Meier methods. Baseline characteristics were compared with Fisher exact tests. Results: Two hundred four consecutive patients (47 minority patients and 157 White patients) were included. Results were presented as minorities versus Whites. There were no differences in prognostic scores (Revised International Prognostic Index score of 3‐5, 43% vs 47%; P  = .50), frontline chemotherapy (98% vs 96%; P  = .68), or the incidence of relapsed/refractory disease (40% vs 38%; P  = .74). For relapsed/refractory LBCL, similar proportions of patients underwent hematopoietic stem cell transplantation (32% vs 29%; P  > .99) or chimeric antigen receptor T‐cell therapy (16% vs 19%; P  > .99). Enrollment in clinical trials was comparable (17% vs 14%; P  = .64). More than 85% received nurse navigation, but minorities had higher intensity navigation encounters (42% vs 21%; P  = .01). The 2‐year OS rates were 81% and 76% for minorities and Whites, respectively ( P  = .27); the 2‐year PFS rates were 62% and 65%, respectively ( P  = .78). Conclusions: This study shows similar survival between Whites and minorities with aggressive LBCL, which was likely due to equal access to guideline‐concordant therapy. Minorities received higher intensity navigation encounters, which may have helped them to overcome socioeconomic disadvantages. Abstract : Although other studies have shown worse outcomes for minorities with aggressive large B‐cell lymphoma, this study demonstrates similar survival in White and minority patients. The authors attribute the equitable outcomes to equal access to guideline‐conforming care and novel treatment options, which may have been attainable by overcoming barriers via the aid of nurse navigation.